Implementation of measures to improve blood collection center employee safety and reduce callouts during the 2019 novel coronavirus pandemic. Issue 8 (3rd May 2021) - Coberly, Emily; Korich, Erin; Henesy, Michelle; Doerksen, Kate; Young, Pampee
Abstract: Background: Blood collection center (BCC) employees are essential workers during the COVID‐19 pandemic. The employee callout rate, defined as the percentage of scheduled employees unable to report to work for any cause including COVID‐19 illness or asymptomatic quarantine, was tracked to determine the impact of safety measures including social distancing, masks, enhanced disinfection protocols, and temperature screening. Study design and methods: A contact tracing and quarantine program was implemented for all employees, followed by additional safety measures including social distancing, masks, enhanced disinfection protocols, and temperature screening. The weekly callout rate was tracked nationally for 19, 517 BCC employees over 9 months, from March to December 2020. Results: Weekly employee callout rates increased after implementation of the contact tracing program due to asymptomatic employees placed into COVID‐19‐related quarantine. Mobile collections callouts increased by nearly fivefold the pre‐pandemic baseline within the first 4 weeks, peaking at 9.7% in early April. Peaks for fixed site collections (5.0%) and manufacturing (6.7%) occurred nearly simultaneously. Shortly after implementation of all safety measures, the weekly callout rate declined for all three employee groups and has remained relatively stable with a mean callout rate of 4.3% for mobile collections, 2.4% for fixed site collections, and 3.7% for manufacturing despite further increase in new COVID‐19 cases in the United States. Conclusion: Callouts for BCC employees during the COVID‐19 pandemic initially increased, but subsequently declined and stabilized after implementation of safety measures. Since multiple interventions were implemented simultaneously, it is not possible to determine the individual impact of each measure on callout rate.